A comparison between flexible electrogoniometers, inclinometers and three-dimensional video analysis system for recording neck movement - Carnaz, Leticia; Moriguchi, Cristiane S.; de Oliveira, Ana Beatriz; Santiago, Paulo R. P.; Caurin, Glauco A. P.; Hansson, Gert-Åke; Gil Coury, Helenice J. C. (Medical Engineering & Physics, 2013)
This study compared neck range of movement recording using three different methods goniometers (EGM), inclinometers (INC) and a three-dimensional video analysis system (IMG) in simultaneous and synchronized data collection. Twelve females performed neck flexion-extension, lateral flexion, rotation and circumduction. The differences between EGM, INC, and IMG were calculated sample by sample. For flexion-extension movement, IMG underestimated the amplitude by 13%; moreover, EGM showed a crosstalk of about 20% for lateral flexion and rotation axes. In lateral flexion movement, all systems showed similar amplitude and the inter-system differences were moderate (4-7%). For rotation movement, EGM showed a high crosstalk (13%) for flexion-extension axis. During the circumduction movement, IMG underestimated the amplitude of flexion-extension movements by about 11%, and the inter-system differences were high (about 17%) except for INC-IMG regarding lateral flexion (7%) and EGM-INC regarding flexion-extension (10%). For application in workplace, INC presents good results compared to IMG and EGM though INC cannot record rotation. EGM should be improved in order to reduce its crosstalk errors and allow recording of the full neck range of movement. Due to non-optimal positioning of the cameras for recording flexion-extension, IMG underestimated the amplitude of these movements. (C) 2013 IPEM. Published by Elsevier Ltd. All rights reserved.
Keywords: Neck pain; Movement; Range of motion; Workplace; Goniometer; Kinematics